Efficiency and Profitability in Chinese Commercial Banks - Li, Jingyuan (2016)
The purpose of this paper is to estimate the efficiency and profitability of commercial banks in China. This paper is based on strong balanced data from 31 selected commercial banks over the period 2010-2015. As for the bank efficiency, the average cost efficiency is 0.6704 and there is a significant growth of annual average efficiency score from 2010 to 2015. And it is clear that state-owned banks are more inefficient that other commercial banks in China. As for the bank profitability, large bank size, high asset quality and liquid assets can contribute to the increase of bank profits while insolvency risk is negatively associated with bank profitability. In addition, the inflation is a strong factor of determining the bank profitability.